The Implementation of the Indonesia-Germany Cooperation: A Case Study of the Community Economic Development Program in Mamasa Subdistrict Through Forest Program IV - Nataniel; Sriwiyata Ismail; Krisman Heriamsal; St. Amaliah Ramli (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2026)
This study aims to analyse the implementation of the Forest Programme IV (FP IV) as a form of Indonesia–Germany cooperation to support community empowerment and environmental management in the buffer zone of Gandang Dewata National Park (TNGD), Mamasa Subdistrict, Mamasa Regency, West Sulawesi Province. This program is part of community-based forest and land rehabilitation efforts in the Mamasa Watershed (DAS) area. The research focuses on the program’s implementation in improving community livelihoods and the challenges encountered during its implementation. This study employs a qualitative case study design. Data were collected through in-depth interviews, field observations, and document analysis. The research analysis employs concepts of international cooperation and community development to understand the relationships among stakeholders and the community empowerment process in the program’s implementation. The results indicate that Forest Program IV in Mamasa Subdistrict was implemented through the provision of business capital support, production tools, and assistance to Forest Farmer Groups (KTH). This program contributed to increasing community economic activities, particularly in agriculture, plantations, honey enterprises, handicrafts, and agroforestry. In addition to increasing community income, the program encouraged community involvement in forest management and environmental conservation within the TNGD buffer zone. However, the program’s implementation still faces several challenges, including limited market access, limited community understanding of the program, mismatches between some activities and community needs, low community participation, and the impact of climate change on the sustainability of community enterprises.